Plant communities of moist rock crevices with endemic Primula carniolica in the (sub)montane belt of western Slovenia - Dakskobler, Igor; Martinčič, Andrej (Hacquetia, 2020)
Based on our analysis of a large number of relevés of communities of moist rock crevices in western Slovenia (southern Julian Alps, northern part of the Trnovski Gozd Plateau) we described several new syntaxa with the endemic Primula carniolica. The most unique in terms of ecology is a hygrophilous chasmophytic community classified into the association Astrantio carniolicae-Primuletum carniolicae, which served, together with similar hygrophilous associations Astrantio carniolicae-Pinguiculetum alpinae and Campanulo cespitosae-Saxifragetum aizoidis, associations Phyteumato columnae-Primuletum carniolicae and Primulo carniolicae-Potentilletum clusianae, and the subassociation Primuletum carniolicae violetosum biflorae, as the basis for the description of the new suballiance Astrantio carniolicae-Paederotenion luteae within the alliance Physoplexido comosae-Saxifragion petraeae. The elevational range of chasmophytic communities with the Natura 2000 species Primula carniolica is 200 to 1460 m a.s.l. Chasmophytic species that most commonly accompany Primula carniolica include Orthothecium rufescens, Paederota lutea, Phyteuma schuechzeri subsp. columnae, Sesleria caerulea and Aster bellidiastrum.